System support and main problems of youth entrepreneurship - Бодаубаева, Г.; Жолдасова A. (Journal of Economic Research & Business Administration, 2017)
Youth Business plays a major role in solving social and economic problems, such as creating new jobs and reducing unemployment, training of qualified personnel. Empowering and enhancing the impact of youth entrepreneurship necessitates the use of its potential. Youth Business is a significant segment of the small business. Young people are the most important link in the business environment. After all, today’s youth, youth entrepreneurship will shape our country in 10 years, the development of today’s youth business will depend on the pace of economic growth and development of our country tomorrow. Thus, to date, youth entrepreneurship is one of the priorities of small business development in Kazakhstan. Creating an enabling environment to encourage young people to engage in entrepreneurial activity is seen in various programs of national and regional level. Considering the above, the article provides predprinematelstva problems of youth. Special attention is paid to supporting youth entrepreneurship.